SANDWICH ELISA FOR TUBERCULAR ANTIGEN DETECTION IN AFB SPUTUM POSITIVE TUBERCULAR PATIENTS IN RURAL BASED TERTIARY CARE HOSPITAL. - AJAY MESHRAM; UDIT AGRAWAL (International Journal of Pharma and Bio Sciences, 2013)
It is estimated that one-third of the world’s population is infected with M. tuberculosis. Also we came to know that the numbers of TB cases are on the rise in our rural based tertiary care hospital. We searched for Mycobacterium tuberculosis antigen in the serum of patients with pulmonary TB by developing Sandwich ELISA. We took 50 pulmonary TB patients, 50 disease control patients, 30 healthy control subjects and 6 extra-pulmonary tubercular patients for our study. We procured the commercial cocktail TB Ag of the mark-Hotgen Biotech and isolated the anti-TB IgG from the sera of TB infected patients. We pooled the well preserved sera samples of TB infected patients for the isolation of anti-TB IgG. We have used anti-TB IgG for the development of Sandwich ELISA for tubercular Ag detection. In 39 out of 50 PTB cases, TB Ag can be detected accurately by our Sandwich ELISA but 16 out of 50 DC cases gave false positive result. Likewise, our test successfully detected TB Ag in 78.12% of PTB cases having 1+ sputum positivity while 83.33% of 2+ and 66.66% of 3+ sputum positive PTB cases. In association with AFB sputum microscopy, the Sandwich ELISA was used as an effective screening test for tuberculosis diagnosis mainly in pulmonary tuberculosis patients.